2007
DOI: 10.1007/s10483-007-0101-x
|View full text |Cite
|
Sign up to set email alerts
|

Complex-mode Galerkin approach in transverse vibration of an axially accelerating viscoelastic string

Abstract: Under the consideration of harmonic fluctuations of initial tension and axially velocity, a nonlinear governing equation for transverse vibration of an axially accelerating string is set up by using the equation of motion for a 3-dimensional deformable body with initial stresses. The Kelvin model is used to describe viscoelastic behaviors of the material. The basis function of the complex-mode Galerkin method for axially accelerating nonlinear strings is constructed by using the modal function of linear moving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Because increasingly used materials such metallic or ceramic reinforced materials exert inherently viscoelastic behaviors, researchers investigate free vibration [2,3], forced vibration [4], and parametric vibrations [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] of axially moving viscoelastic strings. The viscoelastic strings they studied are differential-type materials described by the Kelvin model [2,4,7,8,11,12,14,15,18,20,21,23] or the standard linear solid model [3,6,17,22], as well as integral-type materials defined by the stress relaxation as an exponential function [5,9,10,16,19] or a power function [13]. Actually, the standard linear solid model, which can describe the behavior of linear viscoelastic materials of solid type with limited creep deformation, covers the Kelvin model and the integral-type constitution relation with an exponential relaxation function as special cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because increasingly used materials such metallic or ceramic reinforced materials exert inherently viscoelastic behaviors, researchers investigate free vibration [2,3], forced vibration [4], and parametric vibrations [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] of axially moving viscoelastic strings. The viscoelastic strings they studied are differential-type materials described by the Kelvin model [2,4,7,8,11,12,14,15,18,20,21,23] or the standard linear solid model [3,6,17,22], as well as integral-type materials defined by the stress relaxation as an exponential function [5,9,10,16,19] or a power function [13]. Actually, the standard linear solid model, which can describe the behavior of linear viscoelastic materials of solid type with limited creep deformation, covers the Kelvin model and the integral-type constitution relation with an exponential relaxation function as special cases.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the standard linear solid model, which can describe the behavior of linear viscoelastic materials of solid type with limited creep deformation, covers the Kelvin model and the integral-type constitution relation with an exponential relaxation function as special cases. When differential-type constitutive laws are incorporated, some investigators used the partial time derivative in the viscoelastic constitutive relations [2][3][4][6][7][8]11,12,14,15,20,21,23,24]. However, Mochensturm and Guo [18] demonstrated that the material time derivative should be used to account for the additional "steady state" dissipation of an axially moving viscoelastic string.…”
Section: Introductionmentioning
confidence: 99%
“…There are comprehensive studies on such systems [1][2][3][4][5]. In recent years, much attention has been paid to parametric vibration of traveling systems and transverse parametric vibration of axially accelerating systems has been extensively analyzed [6,7]. Pakdemirli et al [8] conducted a stability analysis using the Floquet theory for sinusoidal transporting velocity function.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies [1][2][3][4][5][6][7][8][9][10][11][12][13] have been performed on the nonlinear dynamics of viscoelastic structures. Chen et al [2][3][4][5] investigated the dynamic stability and chaotic motion of a nonlinear viscoelastic beam and column by applying the Leaderman constitutive relation with Galerkin numerical integration.…”
Section: Introductionmentioning
confidence: 99%
“…Also, other constitutive relations [6][7][8] are adopted to investigate the dynamics of the viscoelastic structures. Moreover, there has been considerable interest in the study of the nonlinear dynamics of the beam [2][3][6][7][8] , column [4][5] , pile [9][10] , plate [11] , shell [12] , and string [13] etc. However, few studies are focused on the nonlinear dynamic behavior of a viscoelastic shallow arch.…”
Section: Introductionmentioning
confidence: 99%